2021
DOI: 10.1007/s40843-020-1615-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into electricity generation from moving ionic droplets on graphene

Abstract: Recent experiments have demonstrated that moving water droplets on polymer-supported graphene can generate electric voltages in graphene. Here, we perform a multi-scale analysis on the mechanism of the generated voltages on the basis of an interplay among the substrate, graphene and ionic water. We find that the attraction of ions in water by substrate dipoles drives charge redistribution in graphene, forming an electric triple layer (ETL) at the water/ graphene/substrate interface, made of an ion layer fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The electric triple layer can well describe the dynamics of coupled ions and electrons at the water/Gr/substrate interface and further quantify the electrical current in graphene. 21 Experimentally, this mechanism was confirmed by measuring the potential distribution in graphene during the dynamic process. After fully immersing graphene in liquids (here, C 1 = C 2 = Á Á Á = C n ), the system reached equilibrium state and the voltage vanished.…”
Section: Mechanismmentioning
confidence: 74%
“…The electric triple layer can well describe the dynamics of coupled ions and electrons at the water/Gr/substrate interface and further quantify the electrical current in graphene. 21 Experimentally, this mechanism was confirmed by measuring the potential distribution in graphene during the dynamic process. After fully immersing graphene in liquids (here, C 1 = C 2 = Á Á Á = C n ), the system reached equilibrium state and the voltage vanished.…”
Section: Mechanismmentioning
confidence: 74%
“…MD simulations performed by Kwon et al 272 have shown that the EDL structure of graphene on a hydrophobic substrate is disordered, originating from the destruction of water dipole assemblies. Recently, Zhang et al 273 performed a multi‐scale analysis on the mechanism of electricity generation from moving ionic droplets on graphene. They found an electric triple layer (ETL) (consist of an ion layer fixed on graphene, an image charge layer in graphene and a counterion layer in water) formed at the water/graphene/substrate interface, due to the attraction of ions in water by substrate dipoles drives charge redistribution in graphene.…”
Section: Simulations For the Applications Of Nanofluidicsmentioning
confidence: 99%
“…[35,36] Then Zhang et al proposed an electric triple layer in which an image charge layer in graphene was considered to couple with the EDL. [37] These novel discoveries have pushed forward the development of the century-old electrokinetic effect.…”
Section: Mechanisms Of Electricity Generationmentioning
confidence: 99%